2011
DOI: 10.1002/app.33785
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chain microstructure on ethylene–norbornene copolymer film properties

Abstract: The effects of copolymer composition, copolymer composition distribution, and polar a-olefin incorporation on transparency, refractive index, and hydrophilicity of resultant ethylene-norbornene copolymer films were investigated. It has been found that the transparency is mainly determined by the copolymer composition distribution. The samples having uniform compositions gave better transparency. However, the copolymer composition distribution had little effect on refractive index. The refractive index increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…35, 36 These investigations showed that an increase in the mol% of norbornene increased the refractive index of the thermoplastic. Liu et al .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…35, 36 These investigations showed that an increase in the mol% of norbornene increased the refractive index of the thermoplastic. Liu et al .…”
Section: Introductionmentioning
confidence: 98%
“…A relationship between norbornene mol% and the refractive index of the substrate has been noted. 35,36 These investigations showed that an increase in the mol% of norbornene increased the refractive index of the thermoplastic. Liu et al also showed that the copolymer composition distribution had a significant effect on the refractive index and transparency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniformity of copolymer composition has a great influence on its property, however, it is very difficult to control unless the copolymerization is conducted in the steady state of the continuous reactor with ideal full back‐mixing. Especially in laboratory research, the copolymerization of monomers with different reactivity is often carried out in a batch reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic olefin copolymers are versatile materials categorized as engineering thermoplastics . The random and alternative attachment of cyclo‐olefins such as cyclohexene, cycloheptene or norbornene into the polyolefinic backbone results in amorphous copolymers with high glass transition temperature, superior transparency, low shrinkage and good mechanical properties .…”
Section: Introductionmentioning
confidence: 99%